Based on t-spherical fuzzy environment: a combination of FWZIC and FDOSM for prioritising COVID-19 vaccine dose recipients - Aos A. Z. Ansaef Al-Juboori (Tanjung Malim, 2021)
Based on t-spherical fuzzy environment: a combination of FWZIC and FDOSM for prioritising COVID-19 vaccine dose recipients by Aos A. Z. Ansaef Al-Juboori